Preparation method and application of double salt doped aluminum adsorbent
By doping metal ions such as iron, calcium, magnesium and other metal ions in the aluminum-based adsorbents to form a complex salt structure, the problem of insufficient capacity and selectivity of the existing aluminum-based adsorbents in the high sulfate brine system is solved, and higher adsorption capacity and selectivity are achieved, and the cycle life is extended.
Patent Information
- Application Number
- CN202510029525.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-25
AI Technical Summary
The existing aluminum-based adsorbents have small adsorption capacity, poor selectivity and short cycle life in the high sulfate brine system, so they cannot be suitable for high sulfate brine system.
By using the combined salt doping method, metal ions such as iron, calcium, magnesium, etc. are incorporated into the aluminum-based adsorbent to form a composite salt structure, and the specific surface area and layer spacing of the adsorbent are increased, thereby improving its capacity and selectivity in the high sulfate brine system.
The capacity and selectivity of aluminum-based adsorbents in the high sulfate brine system are significantly improved, their cycle life is extended, and the selective adsorption capacity of target pollutants is improved.
Smart Images

Figure CN119869491A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium extraction from salt lakes by adsorption method, and relates to a preparation method and application of a double salt-doped modified aluminum-based adsorbent. Background Art
[0002] Aluminum-based adsorbent is a commonly used adsorbent, mainly used to remove pollutants in water, such as heavy metal ions, metal cations, etc. Aluminum-based adsorbents have the advantages of abundant raw materials, low price, and easy preparation, so they have received widespread attention and application. Existing aluminum-based adsorbents can effectively remove impurity ions in water to a certain extent, and are simple to prepare, have a fast adsorption rate, and are widely used in magnesium sulfate subtype brine systems.
[0003] However, the current aluminum salt lithium adsorbent has a small adsorption capacity in high sulfate system brine, the capacity decreases rapidly, the magnesium-lithium ratio in the eluent is high, the magnesium-lithium separation efficiency is low, and the cycle life in the high sulfate system environment is short, and "sulfate poisoning phenomenon" occurs, making the traditional aluminum adsorbent unsuitable for high sulfate brine system. Therefore, it is necessary to provide an aluminum salt lithium adsorbent with high adsorption capacity, high selectivity and high durability in the high sulfate system environment.
[0004] Although existing aluminum-based adsorbents can effectively remove impurity ions in water to a certain extent, there are still some problems with their capacity and selectivity in high sulfate brine systems. First, the capacity of existing aluminum-based adsorbents in high sulfate brine systems is low, which limits their scope of application and use effect. Secondly, the selectivity of existing aluminum-based adsorbents in high sulfate brine systems is poor, which will result in the adsorption of some beneficial ions while removing pollutants, thereby affecting the water quality. Therefore, how to improve the capacity, selectivity and cycle life of aluminum-based adsorbents in high sulfate brine systems is a problem that needs to be urgently solved in this field. Summary of the invention
[0005] In order to solve the above problems, the present technical solution provides a new type of double salt doped aluminum-based adsorbent, which has higher capacity and selectivity and can more effectively remove impurity ions and pollutants in water, such as heavy metal ions, inorganic cations, etc. In addition, the present technical solution provides a new method for preparing double salt doped aluminum-based adsorbent, which has the advantages of simple operation and low cost, and will promote the development of adsorbent preparation technology and promote the development of chemical engineering. In general, the present technical solution has broad application prospects in the fields of materials science, environmental engineering, chemical engineering, etc., has a large market demand, and has important practical value.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a double salt-doped aluminum-based adsorbent, characterized in that it comprises the following steps
[0008] Prepare lithium source solution, aluminum source solution, double salt solution and alkaline solution;
[0009] mixing the lithium source solution and the aluminum source solution to obtain a mixed solution;
[0010] The mixed solution and the alkaline solution are simultaneously added dropwise to the double salt solution to react in a constant temperature water bath;
[0011] After the constant temperature water bath reaction is completed, the mixture is aged and filtered, and the obtained powder is dried and crushed to obtain a double salt-doped aluminum-based adsorbent powder.
[0012] Preferably, the lithium source component in the lithium source solution is at least one of lithium chloride, lithium hydroxide, lithium carbonate, lithium nitrate and lithium sulfate, with a molar ratio of 5-10:0.5-1:0.5-1:0.5-1:0.5-1, and a total lithium concentration of 2-4 mol / L.
[0013] Preferably, the aluminum source component in the aluminum source solution is at least one of hydrated aluminum chloride, sodium metaaluminate, aluminum sulfate, and polyaluminum chloride, with a molar ratio of 5 to 10:1:0.5:0.5 and a concentration of 3 to 5 mol / L.
[0014] Preferably, the complex salt components in the complex salt solution are iron salt, calcium salt and magnesium sulfate, the iron salt is at least one of ferric chloride, ferrous sulfate and ferric nitrate, the calcium salt is at least one of calcium chloride, calcium carbonate and calcium sulfate, wherein the concentration of the iron salt is 0.5-1 mol / L, the concentration of the calcium salt is 0.2-0.5 mol / L, and the concentration of the magnesium sulfate is 0.2-0.5 mol / L.
[0015] Preferably, the alkaline solution is a sodium hydroxide solution with a concentration of 8 to 12 mol / L.
[0016] Preferably, hydrochloric acid is added to the double salt solution to adjust the pH to 5-8, and the solution is heated in a water bath to 70-80° C. The lithium source, aluminum source, and alkaline solution are respectively added to the double salt solution at a flow rate of 1-3:4-6:2, and then the solution is reacted in a constant temperature water bath for 3-5 hours, and the pH of the reaction process is controlled at 5-8.
[0017] Preferably, the aging time is 1 to 3 hours.
[0018] The present invention also provides a double salt-doped aluminum-based adsorbent prepared according to the method.
[0019] The present invention also provides the application of the above-mentioned complex salt doped aluminum series adsorbent, that is, for removing impurity ions and pollutants in water, especially for removing impurity ions and pollutants in high sulfate system brine.
[0020] Compared with the prior art, the main problems solved by this technical solution are:
[0021] 1) Improving the lithium adsorption capacity of aluminum-based adsorbents in high sulfate brine systems;
[0022] 2) Improve the poor selectivity of aluminum-based adsorbents in high sulfate brine systems and the problem of easy poisoning of adsorbents.
[0023] Specifically, compared with the existing technology, the beneficial effects of this technical solution are as follows:
[0024] 1. Improved capacity: The capacity of the double salt-doped aluminum adsorbent in the high sulfate brine system is significantly improved. This is mainly because the doping of double salts changes the structure and composition of the aluminum adsorbent, the petal-like structure on the surface greatly increases the specific surface area, and the increased interlayer spacing of the adsorbent increases the ion transfer rate, thereby improving its adsorption capacity. High-capacity aluminum adsorbents can more effectively remove pollutants in water, thereby improving their application range and use effect.
[0025] 2. Improved selectivity: The selectivity of the double salt-doped aluminum adsorbent of the present invention in the high sulfate brine system is also significantly improved. This is mainly because the doping of double salts changes the functional groups and charge distribution on the surface of the aluminum adsorbent, thereby improving its selective adsorption capacity for target pollutants. Highly selective aluminum adsorbents can more accurately remove pollutants in water, thereby avoiding the adsorption of beneficial ions and improving water quality.
[0026] 3. Extended cycle life: The cycle life of the double salt-doped aluminum-based adsorbent of the present invention in a high sulfate brine system is also significantly extended. This is mainly because the doping of double salts makes the structure and composition of the aluminum-based adsorbent more stable, thereby improving its durability and antioxidant properties in harsh environments. Aluminum-based adsorbents with long cycle life can reduce the frequency of replacement, thereby reducing the cost of use and the difficulty of maintenance. In general, the double salt-doped aluminum-based adsorbent of the present invention has significant advantages over existing aluminum-based adsorbents in terms of increasing capacity, improving selectivity, and extending cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 .Process flow chart of the present invention.
[0028] Figure 2 .SEM image of modified aluminum-based adsorbent powder.
[0029] Figure 3 .XRD diagram of modified aluminum-based adsorbent powder.
[0030] Figure 4 .The mass ratio of each impurity ion to lithium ion in the analytical solution.
[0031] Figure 5 .Changes in lithium extraction capacity of modified aluminum-based adsorbent powder in a higher concentration sulfate system. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below through specific embodiments and drawings.
[0033] This technical solution mainly adopts the following technical means:
[0034] 1. By adopting the method of complex salt doping, a certain proportion of metal ions (such as iron, calcium, magnesium, etc.) are doped into the aluminum-based adsorbent to form a complex salt structure with a more stable layered structure, thereby increasing the capacity of the adsorbent in the high sulfate brine system.
[0035] 2. Optimize the preparation process. By adjusting the preparation process and parameters such as pH value, temperature, and time during the preparation process, the microstructure and morphology of the adsorbent are controlled. The surface of the prepared adsorbent powder has a petal-like structure, which greatly increases its specific surface area, thereby improving the capacity and selectivity of the adsorbent in high sulfate brine systems.
[0036] 3. Conduct systematic experimental evaluation, through static adsorption experiments, dynamic adsorption experiments, cyclic stability experiments, etc., to comprehensively evaluate the performance of the adsorbent in high sulfate brine system and provide data support for practical applications.
[0037] The present invention provides a method for preparing a novel double salt doped aluminum series adsorbent, the process flow of which is as follows: Figure 1 As shown, it includes the following steps:
[0038] Step 1: prepare a lithium source solution; Step 2: prepare a complex salt solution, using iron, calcium salt compounds and magnesium sulfate to prepare the complex salt solution; Step 3: prepare an aluminum source solution; Step 4: mix the lithium source solution and the aluminum source solution prepared above; Step 5: prepare an alkaline solution; Step 6: simultaneously drop the mixed solution and the alkaline solution into the complex salt solution, and react in a constant temperature water bath; Step 7: after the reaction is completed, age and filter the adsorbent precursor, dry and crush it to obtain a modified aluminum-based adsorbent powder.
[0039] The key to the double salt modified aluminum-based adsorbent prepared by the present invention is that the double salt doping causes the change of the structure and charge of the adsorbent itself during the preparation process. Metal ions such as iron, magnesium, and calcium in the double salt can replace part of the aluminum element to form a regular octahedral structure in the positive layer of the adsorbent. The change in charge energy density causes the octahedral structure and arrangement of the positive layer to change. At the same time, during the constant temperature water bath reaction process, part of the magnesium, iron, and calcium metal ions compete with lithium ions and will be inserted into the positive layer. In order to achieve the charge balance between the negative layer and the positive layer, part of the sulfate radical will be inserted into the negative layer, so that the interlayer spacing of the adsorbent is increased, which is conducive to the mass transfer exchange of the negative layer ions. On the other hand, when the lithium source and the aluminum source are slowly added dropwise to the double salt solution, a Li-Al layered double hydroxide crystal nucleus will be formed during the initial reaction. By adjusting the reaction conditions, the lattice growth environment is mild and the crystal nucleus structure is more complete. The target product has a larger specific surface area, increased mass transfer efficiency, and increased adsorption capacity.
[0040] The key points of the present invention are:
[0041] 1) The present invention provides a preparation method and application of a novel double salt-doped aluminum-based adsorbent;
[0042] 2) Double salt doping changes the structure and composition of the adsorbent. The adsorbent surface has a petal-like structure, which greatly increases the specific surface area and improves the lithium adsorption capacity. The increase in the interlayer spacing of the adsorbent increases the mass transfer rate and ion selectivity of the ions.
[0043] 3) The doping of complex salts changes the charge distribution on the surface of aluminum-based adsorbents, thereby improving their selective adsorption capacity for target pollutants.
[0044] Example 1.
[0045] This embodiment specifically discloses a method for preparing a double salt-doped aluminum-based adsorbent, comprising the following steps:
[0046] 1. Prepare a lithium source solution, wherein the lithium source components are lithium chloride, lithium hydroxide and lithium carbonate, the molar ratio is 5:1:1, and the total lithium concentration is 2-4 mol / L;
[0047] 2. Prepare aluminum source solution, the aluminum source components are aluminum chloride hydrate and sodium aluminate, the molar ratio is 10:1, and the concentration is 5 mol / L;
[0048] 3. Prepare a complex salt solution, the complex salt components are ferric chloride and magnesium sulfate, wherein the concentration of ferric chloride is 0.5 mol / L, and the concentration of magnesium sulfate is 0.2 mol / L;
[0049] 4. Prepare an alkaline solution, the alkaline solution consists of sodium hydroxide with a concentration of 8 mol / L;
[0050] 5. Add hydrochloric acid to the above double salt solution to adjust the pH to 5, heat it in a water bath to 70-80°C, mix the lithium source and aluminum source respectively with the alkaline solution and add them to the double salt solution at a flow rate of 1:2, then react in a constant temperature water bath for 3 hours, and control the pH of the reaction process at 5-8;
[0051] 6. After the reaction is completed, the mixture is aged for 1 hour, and the powder obtained after filtration is dried to obtain a double salt modified aluminum adsorbent powder; Example 2.
[0052] This embodiment specifically discloses a method for preparing a double salt-doped aluminum-based adsorbent, comprising the following steps:
[0053] 1. Prepare a lithium source solution, wherein the lithium source components are lithium chloride, lithium hydroxide and lithium carbonate, the molar ratio is 5:1:1, and the total lithium concentration is 2-4 mol / L;
[0054] 2. Prepare aluminum source solution, the aluminum source components are aluminum chloride hydrate and sodium aluminate, the molar ratio is 10:1, and the concentration is 5 mol / L;
[0055] 3. Prepare a complex salt solution, the complex salt components are calcium chloride and magnesium sulfate, wherein the concentration of calcium chloride is 0.2 mol / L, and the concentration of magnesium sulfate is 0.2 mol / L;
[0056] 4. Prepare an alkaline solution, the alkaline solution consists of sodium hydroxide with a concentration of 8 mol / L;
[0057] 5. Add hydrochloric acid to the above double salt solution to adjust the pH to 5, heat it in a water bath to 70-80°C, mix the lithium source and aluminum source respectively with the alkaline solution and add them to the double salt solution at a flow rate of 1:2, then react in a constant temperature water bath for 3 hours, and control the pH of the reaction process at 5-8;
[0058] 6. After the reaction is completed, the mixture is aged for 2 hours, and the powder obtained after filtration is dried to obtain a double salt modified aluminum adsorbent powder; Example 3.
[0059] This embodiment specifically discloses a method for preparing a double salt-doped aluminum-based adsorbent, comprising the following steps:
[0060] 1. Prepare a lithium source solution, wherein the lithium source components are lithium chloride, lithium hydroxide and lithium carbonate, the molar ratio is 10:1:1, and the total lithium concentration is 2-4 mol / L;
[0061] 2. Prepare aluminum source solution, the aluminum source components are aluminum chloride hydrate and sodium aluminate, the molar ratio is 8:1, and the concentration is 5 mol / L;
[0062] 3. Prepare a complex salt solution, the complex salt components are ferric chloride, calcium chloride and magnesium sulfate, wherein the concentration of ferric chloride is 0.5 mol / L, the concentration of calcium chloride is 0.2 mol / L, and the concentration of magnesium sulfate is 0.2 mol / L;
[0063] 4. Prepare an alkaline solution, the alkaline solution consists of sodium hydroxide with a concentration of 8 mol / L;
[0064] 5. Add hydrochloric acid to the above double salt solution to adjust the pH to 5, heat it in a water bath to 70-80°C, mix the lithium source and aluminum source respectively with the alkaline solution and add them to the double salt solution at a flow rate of 1:2, then react in a constant temperature water bath for 3 hours, and control the pH of the reaction process at 5-8;
[0065] 6. After the reaction is completed, the mixture is aged for 1 hour, and the powder obtained after filtration is dried to obtain a double salt modified aluminum adsorbent powder;
[0066] The SEM images of the modified aluminum-based adsorbent powder prepared in this example are as follows: Figure 2 As shown in Figure 1, the surface is a petal-like structure. The XRD pattern of aluminum adsorbent powder is shown in Figure 1. Figure 3 As shown, the material crystal structure is more complete and the interlayer spacing is increased.
[0067] Example 4.
[0068] Taking the actual brine in the deep underground layer of Dongtaijinaier Lake as an example, the components of the deep underground brine of Dongtaijinaier Lake are shown in Table 1. The modified aluminum-based adsorbent in Example 1 is sent into the bed for adsorption. The parameters of the adsorption process are: the flow rate is 20BV / h, and the adsorption ends after 60 minutes of cyclic adsorption. After rinsing the adsorbent with water, a desorption solution with a lithium ion content of 30ppm and a pH of 5-8 is added for desorption. The desorption conditions are a flow rate of 18BV / h and a cyclic analysis of 30 minutes. The changes in ion concentration are shown in Table 1. The results show that the lithium adsorption capacity of the modified aluminum-based adsorbent is 8-10mg / g, and the analysis capacity is 8-10mg / g; the mass ratio of each impurity ion in the analysis solution to the lithium ion is as follows: Figure 4 As shown, the results show that the magnesium ion removal rate is as high as 99.20%.
[0069] Table 1. Original halogen components and ion concentrations of adsorption tail liquid and analytical liquid
[0070]
[0071] Example 5.
[0072] A lithium-containing solution with a higher concentration of sulfate was prepared. The concentrations of other impurity ions were as shown in Example 1. The sulfate concentration was increased to 100 g / L, the Li concentration was controlled at about 500-550 ppm, and the pH was adjusted to about 5.0-6.0 with hydrochloric acid. The specific components of the prepared solution are shown in Table 2. The modified aluminum-based adsorbent of Example 1 was placed in it for a cyclic adsorption experiment, and the lithium extraction effect was shown in Table 2. Figure 5The results show that the modified aluminum-based adsorbent of the present invention can maintain stable lithium extraction in a higher concentration sulfate brine system; this experiment further proves that the modified aluminum-based adsorbent is suitable for high concentration sulfate-containing lithium brine.
[0073] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.
Claims
1. A method for preparing a double salt-doped aluminum-based adsorbent, characterized in that: The following steps are involved: Prepare lithium source solution, aluminum source solution, double salt solution and alkaline solution; mixing the lithium source solution and the aluminum source solution to obtain a mixed solution; The mixed solution and the alkaline solution are simultaneously added dropwise to the double salt solution to react in a constant temperature water bath; After the constant temperature water bath reaction is completed, the mixture is aged and filtered, and the obtained powder is dried and crushed to obtain a double salt-doped aluminum-based adsorbent powder.
2. The method according to claim 1, characterized in that The lithium source component in the lithium source solution is at least one of lithium chloride, lithium hydroxide, lithium carbonate, lithium nitrate and lithium sulfate, the molar ratio is 5-10:0.5-1:0.5-1:0.5-1:0.5-1, and the total lithium concentration is 2-4 mol / L.
3. The method according to claim 1, characterized in that The aluminum source component in the aluminum source solution is at least one of hydrated aluminum chloride, sodium metaaluminate, aluminum sulfate, and polyaluminum chloride, with a molar ratio of 5 to 10:1:0.5:0.5 and a concentration of 3 to 5 mol / L.
4. The method according to claim 1, characterized in that: The complex salt components in the complex salt solution are iron salt, calcium salt and magnesium sulfate, the iron salt is at least one of ferric chloride, ferrous sulfate and ferric nitrate, and the calcium salt is at least one of calcium chloride, calcium carbonate and calcium sulfate.
5. The method according to claim 4, characterized in that The concentration of the iron salt is 0.5-1 mol / L, the concentration of the calcium salt is 0.2-0.5 mol / L, and the concentration of the magnesium sulfate is 0.2-0.5 mol / L.
6. The method according to claim 1, characterized in that The alkaline solution is a sodium hydroxide solution with a concentration of 8 to 12 mol / L.
7. The method according to claim 1, characterized in that The double salt solution is added with hydrochloric acid to adjust the pH to 5-8, heated in a water bath to 70-80° C., and the lithium source, aluminum source and alkali solution are respectively added to the double salt solution at a flow rate of 1-3:4-6:2, and then reacted in a constant temperature water bath for 3-5 hours, and the pH of the reaction process is controlled at 5-8.
8. The method according to claim 1, characterized in that The aging time is 1 to 3 hours.
9. A double salt-doped aluminum-based adsorbent prepared according to the method of any one of claims 1 to 8.
10. The double salt doped aluminum adsorbent according to claim 9 is used to remove impurity ions and pollutants in high sulfate system brine.